Digital communication channels in Industry 4.0 implementation : the role of internal communication - Kovaitė, Kristina (Array, 2020)
Industry 4.0 describes a phenomenon which augments business models and also communication channels in commercial enterprises. This paper analyses scientific publications related to the business model changes driven by Industry 4.0, and also digital internal communication channels used to reduce risks in the process. The paper is based upon a systematic review of scientific publications and evaluation by experts. The research revealed a gap between internal communication through digital channels and the change process in Industry 4.0-driven business models. Each channel has its mission and contributes to reducing risk during the change process. Since there is no universal digital channel for internal communication, different digital communication channels are efficient at different stages of change. The paper makes recommendations for enterprises, related to the effectiveness of digital communication channels during the business model transformation. It further contributes to existing knowledge by expanding the change process model and aligning the change process with features of digital communication channels. The research focused on the manufacturing sector, exploring digital communication channels used to reduce risk during the change process, which is a limitation of this study, along with assumption of a basic level of digital competences in the enterprise.